2022
DOI: 10.1007/s00415-022-11347-w
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in progressive supranuclear palsy

Abstract: Background The degree of involvement of the autonomic nervous system in progressive supranuclear palsy (PSP) has been investigated in several studies, often providing conflicting results. There is a need for a better characterization of autonomic dysfunction in PSP, to enhance our understanding of this highly disabling neurodegenerative disease including patients’ needs and possibly be of value for clinicians in the differential diagnosis among Parkinsonian syndromes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 84 publications
4
15
0
Order By: Relevance
“…Photophobia can also be considered as an autonomic nervous system symptom as is the case in Parkinson's disease, multiple system atrophy, or PSP [34]. It is then often associated with a pupillomotor dysfunction [8]. We described this autonomic involvement in DLB in a previous article, where we demonstrated that DLB patients also had other early neurovegetative disorders, namely rhinorrhea, sicca syndrome, and constipation [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photophobia can also be considered as an autonomic nervous system symptom as is the case in Parkinson's disease, multiple system atrophy, or PSP [34]. It is then often associated with a pupillomotor dysfunction [8]. We described this autonomic involvement in DLB in a previous article, where we demonstrated that DLB patients also had other early neurovegetative disorders, namely rhinorrhea, sicca syndrome, and constipation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Photophobia was first associated with ophthalmological diseases, such as lesions of the cornea, and subsequently with neurologic and neurogeriatric conditions, such as migraine [5], blepharospasm [6], and progressive supranuclear palsy (PSP) [7]. Photophobia, present in 43%-100% of PSP patients [8], appears to cause a reduction in quality of life, with an impact on outdoor activities [9]. Photophobia has been very rarely studied in other neurocognitive diseases.…”
mentioning
confidence: 99%
“…Sudden onset or stepwise progression is suspicious of a vascular cause, while a rapid progression could evoke an autoimmune encephalitis or prion disease. Although PSP patients can report autonomic-like symptoms, they are usually not severe and do not dominate the clinical picture [10].…”
Section: Andandmentioning
confidence: 99%
“…Dysautonomia and the GI symptoms of PSP are not as well-recognized as those occurring in PD, despite the relatively high rate of occurrence and higher severity of symptoms. [147][148][149][150] Some studies suggest that up to 80% of individuals with PSP experience GI symptoms. 151 Though constipation is the most common GI symptom in PD and MSA, dysphagia ranks first in PSP.…”
Section: Progressive Supranuclear Palsymentioning
confidence: 99%